Engaging consumers living in remote areas of Western Australia in the self-management of back pain: A prospective cohort study - Slater, Helen; Briggs, Andrew; Bunzli, Samantha; Davies, S.; Smith, Anne; Quintner, J. (Biomed Central Ltd, 2012)
Background: In Western Australia (WA), health policy recommends encouraging the use of active self-management strategies as part of the co-care of consumers with persistent low back pain (LBP). As many areas in WA are geographically isolated and health services are limited, implementing this policy into practice is critical if health outcomes for consumers living in geographically-isolated areas are to be improved. Methods: In this prospective cohort study, 51 consumers (mean (SD) age 62.3 (±15.1) years) participated in an evidence-based interdisciplinary pain education program (modified Self Training Educative Pain Sessions: mSTEPS) delivered at three geographically isolated WA sites. Self report measures included LBP beliefs and attitudes (Back Pain Beliefs Questionnaire (BBQ); Fear Avoidance Beliefs Questionnaire (FABQ)), use of active and passive self-management strategies, and health literacy, and global perceived impression of usefulness (GPIU) recorded immediately pre-intervention (n = 51), same day post-intervention (BBQ; GPIU, n = 49) and 3 months post-intervention (n = 25).Results: At baseline, consumers demonstrated adequate health literacy and elements of positive health behaviours, reflected by the use of more active than passive strategies in self-managing their persistent LBP. Immediately post-intervention, there was strong evidence for improvement in consumers’ general beliefs about LBP as demonstrated by an increase in BBQ scores (baseline [mean (SD): 25.8 (7.6)] to same day post-intervention [28.8 (7.2); P < 0.005], however this improvement was not sustained at 3 months post-intervention. The majority of consumers (86.4%) reported the intervention as very useful [rated on NRS as 7–10]. Conclusions: To sustain improved consumer beliefs regarding LBP and encourage the adoption of more positive health behaviours, additional reinforcement strategies for consumers living in remote areas where service access and skilled workforce are limited are recommended. This study highlights the need for aligning health services and skilled workforce to improve the delivery of co-care for consumers living in geographically isolated areas.